PENERAPAN APLIKASI PROVINCIAL/ KABUPATEN ROAD MANAGEMENT SYSTEM (PKRMS) PADA KEGIATAN PRESERVASI JALAN DI KABUPATEN SUMBAWA BARAT - ARMAYADI, ARMAYADI; YAMIN, AHMAD; DHARMAWANSYAH, DEDY (GANEC SWARA, 2023)
The database-based one data management policy is used by the West Sumbawa Regency DPUPR community development sector, especially for road infrastructure. Apart from that, the high percentage of unsatisfactory district roads in West Sumbawa shows the need for good management planning to facilitate decision making in implementing district road preservation in West Sumbawa. Through this study, the type and volume of damage to roads and complementary buildings and supporting facilities can be detected early so that immediate treatment can be carried out. This research aims to describe the application of the Provincial/District Road Management System (PKRMS) application. The data presented in this research is field data obtained from the work results (output) of the PKRMS application as a media/tool for conducting road condition surveys as part/item of district road preservation/maintenance activities in West Sumbawa. This research design uses a qualitative method with a survey approach using the Privincial/District Road Management System (PKRMS) application. The results of the research show that the current performance conditions of district roads in West Sumbawa are still far from ideal. This is because several roads have not been 100% treated with preservation. So the program recommendation is periodic maintenance and routine maintenance